The Properties of Dual Acceptor Delta-Doped ZnO Thin Films. Issue 1805 (15th July 2015) - Oder, T N.; Gade, R.C.; Merlo, C.
ABSTRACT: We report the investigation of ZnO thin films delta-doped with lithium and phosphorus introduced simultaneously. The films were deposited from high purity ceramic targets of ZnO and Li3 PO4 on c-plane sapphire substrates by RF magnetron sputtering. An undoped ZnO film with a low background electron concentration was used as the buffer layer on the sapphire substrate. The doped films were prepared by carrying simultaneous sputtering from the ZnO and Li3 PO4 ceramic targets. For uniform doped films, the simultaneous deposition from the ZnO and Li3 PO4 was uninterrupted. For the delta-doped films on the other hand, deposition from the ZnO target was uninterrupted while that from the Li3 PO4 was interrupted periodically using a shutter. Post-deposition annealing was carried using a rapid thermal processor in O2 at 900 o C for 3 min. Results obtained from photoluminescence spectroscopy measurements at 12 K revealed acceptor-related luminescence peaks at 3.35 eV, possibly due to the transition from exciton bound to a neutral acceptor. The x-ray diffraction 2 θ -scans showed a single peak at about 34.4 o . Hall effect measurements revealed p -type conductivities with an average Hall concentrations of 3.8 x 10 13 cm -3 in uniform doped samples and 1.5 x 10 16 cm -3 in delta doped samples. However, in some cases the Hall coefficients had both positive and negative values, making the determination of the carrier type inconclusive. The fluctuation in the carrier type could be due to the lateral inhomogeneity in the hole concentration caused by signal noise impacting the small Hall voltages in the measurements.